The unfixable brain: Confirmation bias and chronic traumatic encephalopathy in football - Ream, Carrington; Jung, Hoyoon (Universitas Tanjungpura, 2025)
Background and Study Aim. Despite strong evidence linking football to chronic traumatic encephalopathy (CTE), skepticism persists among athletes and sport stakeholders. Research suggests individuals often resist health information that challenges core aspects of their identity. Material and Methods. In this study, we examined whether football players demonstrate confirmation bias when evaluating CTE research and whether their responses differ by their level of athletic identification. Participants (N = 72) were randomly assigned to read either a CTE-focused article or a control article on AIDS. They then completed a questionnaire assessing article credibility and agreement with risk-related statements. To assess the potential role of identity-protective reasoning, the study also included a measure of athletic self-concept to evaluate its moderating influence on participants' interpretations. Responses were analyzed both at the group level and at the level of individual item endorsement. Results. Results showed no significant differences in credibility ratings between athlete and nonathlete groups. However, item-level analysis revealed that football players were more likely to agree that playing football is worth the risk of CTE and were less likely to support precautionary reflection. These patterns suggest that identity salience may drive selective acceptance of health information. Although football players may accept the scientific legitimacy of CTE, they interpret its implications in ways that protect their athletic identity and justify continued participation. Conclusions. The study contributes to ongoing discussions about risk rationalization, identity-protective cognition, and resistance to health messaging in athletic contexts. Findings also underscore the importance of tailoring health communication to align with the values and commitments of sport-identified populations.